Phad of the Phad: Reading and Writing of the Ritual Craft (Proceeding of the International Conference on Arts and Humanities, 2020)
The primary objective of this paper is an attempt to understand the ‘Liminal Quality of the Ritual’ with reference to the Phad painting i.e. famous folk craft of Rajasthan. Phad painting majorly divided into three components which are, visual (imagery), oral (story telling) and performative. How these three components are interconnected? And how each component is changing according to the evolving communities? There is an urgency to record and understand these facts, keeping in mind this study is an attempt to explore about the origin of this folk tradition and it’s contemporisation. The other objective of this study is to communicate what the Modern/Urban community communicates through their oral narratives and through their folk mediums. During research the findings have suggested that most of the time these local deities are the incarnation of Greater God to develop the connection between great tradition and little traditions.1In today’s scenario cotemporary tales, myths, stories, talks about the current issues of the modern communities. And these modern communities have modern Gods, such as Om Banna JI who is recently developed ‘Folk God’ of Rajasthan of Pali district near Jodhpur. The new God addresses the modern issues and sometimes old folk Gods such as Papuji or Teja ji etc also deal with prevailing issues of the communities. These stories, myths are shifting, symbols, signs, meanings are also shifting, and resulting the so called “Traditional Craft” is also shifting towards the contemporisation.
Keywords: Phad Painting; After Life of the Craft or Contemporary Craft; Visual Ethnography; Great and little traditions